Necrotizing fasciitis in the form of Fournier gangrene in a 70 year old patient: Nekrozantni fasciitis v obliki Fourniejeve gangrene pri 70 let starem pacientu - Arslani, Nuhi; Mikuljan, Timotej (Acta Medico-Biotechnica, 2021)
Purpose: In this case report, we describe a patient with Fournier gangrene, as well as his treatmentcourse and management.Case report: A 70-year-old male was hospitalized for Fournier gangrene in the perianal region. We performed radical necrectomy, drainage of perianal abscess, and transversostomy. Based on wound culture results, Amoksiklav and Ciprobay were administered. The complication of decompensated adhesive ileus occurred, which required reoperative intervention.Conclusion: Fournier gangrene is a rare disease that usually affects males. The disease begins withswelling, cellulitis, fever, and odor. We successfully treated this disease with emergency surgery and reoperative intervention.
Keywords: decompensated adhesive ileus; necrotizing fasciitis; necrectomy; exploratory laparotomy